Specialized Hospitals To Faced The Epidemic Beri-Beri On The War In Aceh - Wahyu Suri Yani (Masyarakat Indonesia, 2020)
The epidemic beri-beri on the war in Aceh effect in high mortality on the Dutch army. The emergence of beri-beri as a contagious disease triggers the government to evacuate patients and establishing a special hospital in Sumatra Westkust. However, indigenous people never known and not infected the epidemic beri-beri. Treatment in special hospitals as a new epidemic became the main solution of the beri-beri problem which also had spread in various centers of the Dutch East Indies government. Through the evidence in Algemene Secreterie Atjeh Zaken, Geneeskundig Tijdschrift voor Nederlandsch Indies archive and other primary sources, indicate that the existence of specialized hospitals has solved the beri-beri problem. This historical research reconstructs the importance of the policy beri-beri hospitals and medical management to encounter of epidemics. The results also showed that discourse and topography of health in Sumatra Westkust with the locality approach became part of a long process to the discovery of anti-beri-beri or thiamine.